Manipulating the Postharvest Period and Its Impact on Vine Productivity of Semillon Grapevines - Holzapfel, B.; Smith, J.; Mandel, Roger; Keller, M. (American Society for Enology and Viticulture, 2006)
Trials were established in four Semillon hot-climate vineyards to determine the importance of the postharvest period for vines grown under different cropping levels and management practices. Two sites were chosen in high-yielding, furrow-irrigated vineyards in the Riverina region, and two in lower-yielding, drip-irrigated vineyards in the neighboring Hilltops region of New South Wales, Australia. Treatments were imposed over two consecutive seasons to alter either the length or the effectiveness of the postharvest period at each site. Complete defoliation at harvest to eliminate carbon assimilation during the postharvest period decreased yields by up to 21% relative to the control vines after one season and by 50% after two seasons of treatment. Extending the length of the postharvest period by early crop removal over two consecutive seasons increased yields by 48% when fruit was retained to commercial maturity in the third year. Vegetative growth responded similarly, and vine balance was not altered by any treatment. Berry sugar concentration at harvest was highest for previously defoliated vines and lowest for vines with an extended postharvest period. Treatments were less effective at the Hilltops vineyards, where lower yields and water availability may have reduced the importance of the postharvest period. Leaf damage or leaf spray applied after harvest did not impact vine productivity. Results suggest that adequate postharvest recovery is crucial for maintaining the productivity of high-yielding grapevines and that vineyards could be managed after harvest to manipulate vegetative growth and yield in the following season.